Incidence and Predictors of Complications During Cryoballoon Pulmonary Vein Isolation for Atrial Fibrillation. Issue 7 (July 2016) - Guhl, Emily N.; Siddoway, Donald; Adelstein, Evan; Bazaz, Raveen; Mendenhall, George S.; Nemec, Jan; Saba, Samir; Schwartzman, David; Voigt, Andrew; Wang, Norman C.; Jain, Sandeep K.
Abstract : Background: Cryoballoon pulmonary vein isolation (PVI) has emerged as an alternative to radiofrequency PVI for atrial fibrillation (AF). Data are lacking to define the rates and predictors of complications, particularly phrenic nerve injury (PNI). Methods and Results: We evaluated a single‐center prospective registry of 450 consecutive patients undergoing cryoballoon PVI between 2011 and 2015. Patients were 59±10 years old, 26% were women, 58% had hypertension, their mean CHA2 DS2 VASc score was 1.7±1.3, 30% had persistent atrial fibrillation, and 92% received a second‐generation 28‐mm balloon. Predefined major complications were persistent PNI, pericardial effusion, deep vein thrombosis, arteriovenous fistula, atrioesophageal fistula, bleeding requiring transfusion, stroke, and death. PNI was categorized as persistent if it persisted after discharge from the laboratory. Logistic regression was performed to identify predictors of complications and specifically PNI. We identified a major complication in 10 (2.2%) patients. In 49 (10.8%) patients, at least transient PNI was observed; only 5 persisted beyond the procedure (1.1%). All cases of PNI resolved eventually, with the longest time to resolution being 48 days. We also describe 2 cases of PNI manifesting after the index hospitalization. Regression analysis identified 23‐mm balloon use (16.3% versus 5.2%, odds ratio 2.94, P =0.011) and increased age (62.8±7.7 versus 58.7±0.12 years, odds ratio 1.058, P =0.014) as independent significant predictors of PNI. There were no significant predictors of major complications. Conclusions: In a large contemporary cohort, cryoballoon PVI is associated with low procedural risk, including lower rates of PNI than previously reported. Older age and 23‐mm balloon use were associated with PNI. Our low rate of PNI may reflect more sensitive detection methods, including compound motor action potential monitoring and forced double‐deflation.